1993
DOI: 10.1073/pnas.90.10.4738
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of the human trithorax-like gene 1 involved in acute leukemias.

Abstract: The human trithorax-like gene 1 (Htrxl gene) is disrupted in 11q23 translocations that are associated with acute leukemias. Sequencing ofa partial human cDNA revealed an open reading frame encoding 1012 amino acids with extensive homology to the Drosophila trithorax protein, particularly in the zinc finger-like domains. Htrxl gene appears to be unique in the human genome and has been conserved during evolution. Use of the human cDNA as a probe demonstrates that this gene is interrupted in both infant and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The central region of trx contains nine cysteine-rich zinc-binding motifs that form three major clusters and a fourth one containing a single motif (51). The cysteine residues and some flanking sequences of clusters II and III are highly conserved in the human homolog of trx (28,62,79). The second conserved region resides in the C terminus (see the introduction).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The central region of trx contains nine cysteine-rich zinc-binding motifs that form three major clusters and a fourth one containing a single motif (51). The cysteine residues and some flanking sequences of clusters II and III are highly conserved in the human homolog of trx (28,62,79). The second conserved region resides in the C terminus (see the introduction).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the observation that highlevel activity of the Ubx promoter supported by trx can be largely repressed by Pc in a dose-dependent manner is consistent with genetic studies that suggest an antagonistic interaction between trx and Pc. Furthermore, the functional role of the highly conserved central zinc-binding domain of trx has been implicated by the following observations: (i) an out-offrame deletion (in the trx B11 allele) before this domain results in loss of function, but an in-frame deletion encompassing the zinc-binding cluster IV (in the trx E3 allele) has no drastic effect on Ubx expression (51); and (ii) disruptions of the human homolog of trx caused by chromosomal translocations are frequently found in this domain (28,62,79). Genetic studies have suggested that complex mechanisms are involved in Ubx regulation by maintenance genes (6,40,59,60).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12] To date, 13 genes involved in translocations with MLL have been cloned. [13][14][15][16][17][18][19][20][21][22][23][24][25] It has been suggested that alteration of the MLL protein is the critical event in oncogenesis and that fusion partners may not play an important role in the oncogenic process. 26,27 MLL gene rearrangements are associated with acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), and secondary acute leukemias.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The structural features of MLL protein, which is highly homologous to Drosophila trithorax protein, suggest that its normal function may be mediated by a physical interaction with DNA. 9,10 Although several chromosome loci are involved in reciprocal 11q23 translocations, t(4;11)(q21;q23) is the most common translocation in infant ALL. 11 In acute leukemia with t(4;11)(q21;q23), the MLL gene on 11q23 usually fuses to the AF-4 (or FEL) gene localized on chromosome band 4q21.…”
Section: Introductionmentioning
confidence: 99%